Preparation method of biphase hard nanoparticle reinforced nodular cast iron applied to lost foam casting
By using the disappearing mold casting method and TiC-TiB2 biphasic hard nanoparticles in ductile iron, the problem of difficulty in improving the strength and toughness of ductile iron at the same time is solved, and the comprehensive performance of the material is improved and the processing process is simplified.
Patent Information
- Application Number
- CN202411402470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to improve strength and toughness simultaneously in ductile iron, and traditional toughening methods often reduce toughness while increasing strength.
Using the disappearing mold casting method, TiC-TiB2 biphasic hard nanoparticles are evenly dispersed into the ductile iron matrix. Through specific process steps and material treatment, ensure that the nanoparticles are evenly distributed during the casting process and effectively improve the nucleation of the material. rate and grain refinement.
The mechanical properties and wear resistance of ductile iron are synergistically improved, the comprehensive performance of the material is enhanced, and the processing process is simplified.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance casting ductile iron preparation, in particular to a preparation method of dual-phase hard nano-particle reinforced ductile iron used in lost foam casting. Background Art
[0002] Ductile iron is one of the important cast iron materials. The graphite structure in its matrix is spherical and has excellent casting and mechanical properties. With the rapid development of industrial technology, industries such as automobiles, mining equipment, ships and infrastructure construction have put forward higher requirements on the performance of ductile iron. In addition to requiring it to have high strength and toughness, it also requires it to have good wear resistance. At present, conventional methods for strengthening and toughening cast iron materials include molten iron purification, alloying, heat treatment and plastic deformation, but these traditional methods are difficult to achieve a synergistic improvement in strength and plasticity, especially when the strength of ductile iron is significantly improved, its toughness will be greatly reduced. In recent years, the development of nanotechnology has provided a new way to strengthen and toughen cast iron materials. Due to their unique size effect, surface effect and quantum effect, nanoparticles can enter the microstructure to regulate phase change and precipitation, thereby affecting the service performance of cast iron materials. Summary of the invention
[0003] In order to overcome the defects of the prior art, the present invention provides a preparation method of dual-phase hard nanoparticle reinforced ductile iron for lost foam casting. Among the numerous hard nanoparticles, TiC and TiB2 nanoparticles have become ideal reinforcing phases for metal-based composite materials due to their advantages such as high hardness, high melting point, high modulus and good chemical stability. Therefore, based on the excellent casting performance of ductile iron, ductile iron containing dual-phase hard nanoparticle dispersion reinforcement is prepared by using lost foam casting in special casting. This method can not only improve the comprehensive performance of ductile iron, but also use lost foam casting to produce various complex parts and components, improve the surface finish of parts, greatly simplify the processing flow and difficulty, break through the limitations of traditional strengthening methods, and provide new ideas for the development of high-performance ductile iron materials and the manufacturing and application of ductile iron parts.
[0004] The technical solution adopted by the present invention to solve its technical problem is:
[0005] A method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting comprises the following steps:
[0006] Step 1: Use a titanium source, a carbon source, and a boron source as precursors, wherein TiCl4 is used as the titanium source, CH4 is used as the carbon source, and B2H6 is used as the boron source. TiCl4 is slowly heated to 40°C until the gas is volatilized, and the volume ratio of TiCl4, CH4, and B2H6 is adjusted to 2:1:1 through a gas flow meter, and uniformly introduced into a high-temperature reactor filled with argon gas, and the temperature is set between 1300°C and 1400°C. TiC-TiB2 dual-phase hard nanoparticles are simultaneously deposited at the bottom of the high-temperature reactor through gas reaction, and the TiC-TiB2 dual-phase hard nanoparticles are blown out of the high-temperature reactor by the flow of argon gas and collected;
[0007] Step 2: The prepared TiC-TiB2 dual-phase hard nanoparticles are repeatedly rinsed with hydrochloric acid to remove surface oxides and impurities; the rinsed TiC-TiB2 dual-phase hard nanoparticles are then rinsed with distilled water for 3 times to further remove surface impurities, and then placed in a drying furnace for drying;
[0008] Step 3, putting the purified TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer into a ball mill together, the ball milling time is 10 to 12 hours, and the ductile iron inoculant and spheroidizer are fully ground at the same time;
[0009] Step 4: Place the nanoparticle-aluminum powder-inoculant-spheroidizer mixture after ball milling activation into alcohol, vibrate it using an ultrasonic cleaner for 40 to 60 minutes, and then place it in a drying furnace for drying;
[0010] Step 5: Redissolve the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer in alcohol, and after sufficient stirring, use an ultrasonic homogenizer to disperse the mixture for 30 to 40 minutes to evenly disperse the mixture in the alcohol;
[0011] Step 6: slowly put the block polystyrene material into the alcohol solution containing the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer, and use an ultrasonic homogenizer to disperse the nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture for 60 to 80 minutes;
[0012] Step 7: Place the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture in a vacuum drying oven and slowly evaporate it until all the liquid evaporates, then take out the remaining polystyrene containing nanoparticles, aluminum powder, inoculant and spheroidizer, and cut the polystyrene into corresponding models according to the casting structure design; mix the refractory coating and water to a suitable viscosity, then evenly apply it on the surface of the polystyrene model, dry the polystyrene model, and then apply it again and dry it, repeating 3 times in total; finally, the thickness of the refractory coating on the surface of the polystyrene model is about 1 to 1.2 mm;
[0013] Step 8: bury the polystyrene mold coated with refractory coating in fine sand, tap the fine sand to fix the mold, and after the mold is fixed, vibrate the mold in the X, Y, and Z directions at the same time for 30 to 50 seconds;
[0014] Step nine: melt the molten iron in a medium frequency induction furnace at a temperature of 1530°C to 1540°C, and then slowly introduce the molten iron into a mold containing polystyrene through a pouring gate. After the mold cools, take out the casting and remove the sand, and finally obtain reinforced ductile iron containing dual-phase hard nanoparticles.
[0015] Preferably, in step 2, the volume fraction of hydrogen chloride in the hydrochloric acid solution used is 30% to 35%.
[0016] Preferably, in the step three, the aluminum powder used has a purity of 99.5wt%; the ductile iron inoculant used is a silicon-calcium inoculant, whose components consist of the following weight percentages: 72.10wt% silicon, 11.51wt% calcium, 1.42wt% barium, 0.74wt% aluminum, and the balance is iron. The amount of the silicon-calcium inoculant added is 0.45wt% of the mass of the molten iron; the spheroidizer used is a rare earth magnesium-silicon-iron alloy, whose components consist of the following weight percentages: 41.30wt% silicon, 8.22wt% magnesium, 6.22wt% cerium, 1.92wt% calcium, and the balance is iron. The amount of the spheroidizer added is 1.3wt% of the mass of the molten iron.
[0017] Preferably, in step 4, the power of the ultrasonic cleaner used is 200W, the vibration frequency is 1kHz, the rotation speed of the ball mill used is 50rpm, the drying furnace used is a quartz tube drying furnace with a power of 450W, and the drying temperature is 130°C to 150°C.
[0018] Preferably, in step five, the power of the ultrasonic homogenizer used is 500 W, the operating frequency is 10 kHz, and the ethanol content in the alcohol solution used is 99.7%.
[0019] Preferably, in step six, the ethanol content in the alcohol solution used is 99.7%, and the amount used is 2.0 to 2.5 L.
[0020] Preferably, in step six, the block polystyrene material used has a length×width×height of 100 mm×100 mm×200 mm.
[0021] Preferably, in the step seven, the components of the refractory coating used are composed of the following weight percentages: 62wt% zircon sand, 20wt% sodium silicate, 8wt% bentonite, 8wt% water, 1.5wt% dispersant, and 0.5wt% defoamer, the dispersant is carboxymethyl cellulose, and the defoamer is silicone oil. The preparation step includes: after the zircon sand, sodium silicate and bentonite are fully mixed, water is added and continuous stirring is continued, after the mixture is evenly mixed, the dispersant and defoamer are added, and continuous stirring is continued until the mixture is evenly mixed.
[0022] Preferably, in step seven, the power of the vacuum drying oven used is 1000W, the drying temperature is 40°C to 50°C, and the drying time is 20 to 30 minutes.
[0023] Preferably, in step nine, the molten iron used is composed of the following weight percentages:
[0024] 3.64wt% carbon, 2.78wt% silicon, 0.40wt% manganese, 0.003wt% phosphorus, 0.015wt% sulfur, 0.035wt% magnesium, 0.012wt% titanium, 0.015wt% aluminum, and the balance is iron.
[0025] The preparation principle of the present invention is as follows: the present invention uniformly disperses TiC-TiB2 two-phase hard nanoparticles into a spherical graphite cast iron matrix through a lost foam casting method, uses polystyrene as a lost foam raw material, and fully mixes the nanoparticles, aluminum powder, inoculant, spheroidizer and polystyrene through the dissolution effect of alcohol on polystyrene. During the casting process, the high temperature of the molten iron causes the polystyrene model to be rapidly vaporized. At the same time, the nanoparticles, spheroidizer and inoculant are uniformly dispersed in the molten iron as the polystyrene is vaporized, and the aluminum powder is combined with oxygen in the molten iron to be suspended on the surface of the molten iron in the form of slag, thereby effectively reducing the oxygen content of the molten iron. During the solidification process, the nanoparticles can serve as the nucleation cores of graphite nodules and austenite, effectively improving the nucleation rate, and further refining the primary phase. In the subsequent solid phase transformation process, the fine austenite can further refine the pearlite and ferrite, and some of the nanoparticles in the matrix will also become the nucleation cores of ferrite and pearlite, thereby refining the cast structure. When ductile iron is subjected to external load, the refined grains and increased grain boundaries will make the force on ductile iron more uniform, reduce the stress concentration area, and cause more uniform deformation, and improve the elongation. Due to the presence of nanoparticles inside the matrix, the second phase will increase the local dislocation density. When the dislocation slips in the matrix, the added nanoparticles, increased dislocations and grain boundaries will have a certain hindering effect on the dislocation slip, so that the dislocation movement consumes more energy, and the strength of ductile iron is improved. When ductile iron is subjected to impact load, large-size cracks will be dispersed into multiple small cracks by nanoparticles and grain boundaries, delaying the expansion of cracks and improving the impact toughness of ductile iron. In the wear test, due to the increase in the strength of the ductile iron matrix after adding nanoparticles, cracks are not easy to initiate, sub-surface dislocations are difficult to slip, and the plastic deformation of the surface and sub-surface is reduced. At the same time, some nanoparticles peeled off from the matrix will act on the contact surface of the friction pair to hinder local direct contact and bear part of the external load, reducing the wear of ductile iron. The mechanical properties and wear resistance of ductile iron can be synergistically improved through the above-mentioned strengthening and toughening method.
[0026] The beneficial effects of the present invention are mainly manifested in: the preparation process is simple, the casting equipment and process are not changed, and the nanoparticles are evenly dispersed, and the mechanical properties and wear resistance of the obtained nanoparticle-reinforced ductile iron are significantly improved; by adding TiC-TiB2 two-phase hard nanoparticles into the lost foam model, during the casting process, the nanoparticles gradually enter the molten iron as the model melts, effectively improving the nucleation rate of the primary structure of the ductile iron, refining the grains, and improving the toughness of the matrix; the nanoparticle-reinforced ductile iron can be widely used in the fields of automobiles, mining equipment, ships, and infrastructure construction. DETAILED DESCRIPTION
[0027] The present invention is further described below.
[0028] A method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting comprises the following steps:
[0029] Step 1: Use a titanium source, a carbon source, and a boron source as precursors, wherein TiCl4 is used as the titanium source, CH4 is used as the carbon source, and B2H6 is used as the boron source. TiCl4 is slowly heated to 40°C until the gas is volatilized, and the volume ratio of TiCl4, CH4, and B2H6 is adjusted to 2:1:1 through a gas flow meter, and uniformly introduced into a high-temperature reactor filled with argon gas, and the temperature is set between 1300°C and 1400°C. TiC-TiB2 dual-phase hard nanoparticles are simultaneously deposited at the bottom of the high-temperature reactor through gas reaction, and the TiC-TiB2 dual-phase hard nanoparticles are blown out of the high-temperature reactor by the flow of argon gas and collected;
[0030] Step 2: The prepared TiC-TiB2 dual-phase hard nanoparticles are repeatedly rinsed with hydrochloric acid to remove surface oxides and impurities; the volume fraction of hydrogen chloride in the hydrochloric acid solution used is 30% to 35%; the rinsed TiC-TiB2 dual-phase hard nanoparticles are then rinsed with distilled water for 3 times to further eliminate surface impurities, and then placed in a drying furnace for drying;
[0031] Step 3, the purified TiC-TiB2 two-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer are put into a ball mill together, the ball milling time is 10-12 hours, and the ductile iron inoculant and spheroidizer are fully ground at the same time; the aluminum powder purity used is 99.5wt%, the ductile iron inoculant used is a silicon-calcium inoculant, and its composition consists of the following weight percentages: 72.10wt% silicon, 11.51wt% calcium, 1.42wt% barium, 0.74wt% aluminum, and the balance is iron. The amount of silicon-calcium inoculant added is 0.45wt% of the mass of molten iron; the spheroidizer used is a rare earth magnesium-silicon-iron alloy, and its composition consists of the following weight percentages: 41.30wt% silicon, 8.22wt% magnesium, 6.22wt% cerium, 1.92wt% calcium, and the balance is iron. The amount of spheroidizer added is 1.3wt% of the mass of molten iron.
[0032] Step 4: Place the nanoparticle-aluminum powder-inoculant-spheroidizer mixture after ball milling activation into alcohol, vibrate it with an ultrasonic cleaner for 40 to 60 minutes, and then place it in a drying furnace for drying; the power of the ultrasonic cleaner used is 200W, the vibration frequency is 1kHz, the speed of the ball mill used is 50rpm, the drying furnace used is a quartz tube drying furnace with a power of 450W, and the drying temperature is 130°C to 150°C.
[0033] Step 5: Redissolve the nanoparticle-aluminum powder-inoculant-spheroidizer mixture in alcohol, and after sufficient stirring, use an ultrasonic homogenizer to disperse the mixture for 30 to 40 minutes to evenly disperse the mixture in the alcohol; the power of the ultrasonic homogenizer used is 500 W, the operating frequency is 10 kHz, and the ethanol content in the alcohol solution used is 99.7%.
[0034] Step six, slowly put the block polystyrene material into the alcohol solution containing the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer, and use an ultrasonic homogenizer to disperse the above nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture for 60 to 80 minutes; the ethanol content in the alcohol solution used is 99.7%, the amount used is 2.0 to 2.5L, and the length × width × height of the block polystyrene material used is 100mm × 100mm × 200mm.
[0035] Step 7, the nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is placed in a vacuum drying oven and slowly evaporated until all the liquid evaporates, and the remaining polystyrene containing nanoparticles, aluminum powder, inoculant and spheroidizer is taken out, and the polystyrene is cut into corresponding models according to the structural design of the casting; the refractory coating and water are mixed to a suitable viscosity, and then evenly applied to the surface of the polystyrene model, and the polystyrene model is dried, and then applied again and dried, and repeated 3 times; the final refractory coating thickness on the surface of the polystyrene model is about 1 to 1.2 mm; the vacuum drying oven power used is 1000 W, the drying temperature is 40°C to 50°C, and the drying time is 20 to 30 min. The components of the refractory coating used are composed of the following weight percentages: 62wt% zircon sand, 20wt% sodium silicate, 8wt% bentonite, 8wt% water, 1.5wt% dispersant, and 0.5wt% defoamer. The dispersant is carboxymethyl cellulose, and the defoamer is silicone oil. The preparation steps include: fully mixing the zircon sand, sodium silicate and bentonite, adding water and continuously stirring, adding the dispersant and defoamer after the mixture is evenly mixed, and continuing to stir until the mixture is evenly mixed.
[0036] Step 8: bury the polystyrene mold coated with refractory coating in fine sand, tap the fine sand to fix the mold, and after the mold is fixed, vibrate the mold in the X, Y, and Z directions at the same time for 30-50 seconds;
[0037] Step nine, use a medium frequency induction furnace to melt the molten iron at a temperature of 1530°C to 1540°C, and then slowly introduce the molten iron into a casting mold containing polystyrene through a pouring gate, wherein the molten iron used is composed of the following weight percentages: 3.64wt% carbon, 2.78wt% silicon, 0.40wt% manganese, 0.003wt% phosphorus, 0.015wt% sulfur, 0.035wt% magnesium, 0.012wt% titanium, 0.015wt% aluminum, and the remainder is iron; after the casting mold is cooled, take out the casting and shake out the sand, and finally obtain reinforced ductile iron containing dual-phase hard nanoparticles.
[0038] Embodiment 1, namely the best embodiment:
[0039] A method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting comprises the following steps:
[0040] Step 1: Use a titanium source, a carbon source, and a boron source as precursors, wherein TiCl4 is used as the titanium source, CH4 is used as the carbon source, and B2H6 is used as the boron source. TiCl4 is slowly heated to 40°C until the gas is volatilized, and the volume ratio of TiCl4, CH4, and B2H6 is adjusted to 2:1:1 through a gas flowmeter, and uniformly introduced into a high-temperature reactor filled with argon gas, and the temperature is set to 1350°C. TiC-TiB2 dual-phase hard nanoparticles are simultaneously deposited at the bottom of the high-temperature reactor through gas reaction, and the TiC-TiB2 dual-phase hard nanoparticles are blown out of the high-temperature reactor by the flow of argon gas and collected;
[0041] Step 2: The prepared TiC-TiB2 dual-phase hard nanoparticles are repeatedly rinsed with hydrochloric acid to remove surface oxides and impurities; the rinsed TiC-TiB2 dual-phase hard nanoparticles are then rinsed with distilled water for 3 times to further remove surface impurities, and then placed in a drying furnace for drying;
[0042] Step 3, weighing 0.03wt% of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer into a ball mill for 11 hours to prevent the formation of large hard particles and fully grind the ductile iron inoculant and spheroidizer;
[0043] Step 4: Place the nanoparticle-aluminum powder-inoculant-spheroidizer mixture after ball milling activation into alcohol, vibrate it using an ultrasonic cleaner for 50 minutes, and then place it in a drying furnace for drying;
[0044] Step 5: Re-dissolve the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer in alcohol, and after sufficient stirring, use an ultrasonic homogenizer to disperse the mixture for 35 minutes to evenly disperse the mixture in the alcohol;
[0045] Step 6: slowly place the block polystyrene material into an alcohol solution containing a mixture of nanoparticles-aluminum powder-inoculant-spheroidizer, and use an ultrasonic homogenizer to disperse the nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture for 70 minutes.
[0046] Step seven, the nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is placed in a vacuum drying oven and slowly evaporated until all the liquid evaporates, and the remaining polystyrene containing nanoparticles, aluminum powder, inoculant and spheroidizer is taken out, and the polystyrene is cut into corresponding models according to the structural design of the casting; the refractory coating and water are mixed to a suitable viscosity, and then evenly applied on the surface of the polystyrene model, and the polystyrene model is dried, and then applied again and dried, and repeated 3 times; finally, the thickness of the refractory coating on the surface of the polystyrene model is about 1 mm.
[0047] Step 8: bury the polystyrene mold coated with refractory coating in fine sand, tap the fine sand to fix the mold, and after the mold is fixed, vibrate the mold in the X, Y, and Z directions at the same time for 40 seconds.
[0048] Step nine: melt the molten iron in a medium frequency induction furnace at a temperature of 1530°C, and then slowly introduce the molten iron into a mold containing polystyrene through a pouring gate. After the mold cools, take out the casting and remove the sand, and finally obtain reinforced ductile iron containing dual-phase hard nanoparticles.
[0049] Comparative Example 1:
[0050] Preparation of ductile iron without TiC-TiB2 dual-phase hard nanoparticles using conventional lost foam casting:
[0051] (1) Melt molten iron in a medium frequency induction furnace at a temperature of 1530° C. Cut the polystyrene raw material into small pieces of 100 mm (length) × 100 mm (width) × 200 mm (height).
[0052] (2) Add 0.45wt% of 75 ferrosilicon inoculant and 1.3wt% of rare earth magnesium alloy spheroidizer into the ladle, and preheat the ladle to 320°C. Mix the refractory coating and water to a suitable viscosity, and evenly apply it on the surface of the block polystyrene, dry it, and apply it again. Repeat the application and drying for 3 times. The final thickness of the refractory coating on the polystyrene surface is about 1mm.
[0053] (3) The polystyrene model coated with refractory coating is buried in fine sand, and the fine sand is struck to fix the mold. After the mold is fixed, vibration is applied to the mold in the X, Y, and Z directions simultaneously for 40 seconds.
[0054] (4) Pour the molten iron into a ladle and stir it thoroughly until the surface of the molten iron is calm. Then, slowly introduce the molten iron into a mold containing polystyrene through a pouring gate. After the mold cools, take out the casting and remove the sand to obtain ductile iron using a conventional lost foam casting method.
[0055] Comparative Example 2:
[0056] Preparation of ductile iron without TiC-TiB2 dual-phase hard nanoparticles using lost foam casting:
[0057] (1) The treatment conditions of ductile iron inoculant and spheroidizer are the same as those in the best case;
[0058] (2) The process flow of lost foam casting is the same as that of the optimal example.
[0059] Example 2, i.e. Comparative Example 3:
[0060] Reinforced ductile iron containing 0.01wt% TiC-TiB2 dual-phase hard nanoparticles was prepared using lost foam casting:
[0061] (1) The preparation and purification of TiC-TiB2 dual-phase hard nanoparticles are the same as those in the best example;
[0062] (2) weighing 0.01 wt% of the nanoparticles by weight of the molten iron;
[0063] (3) The mixing method of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer is the same as that of the optimal example;
[0064] (4) The preparation process of the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is the same as that of the optimal example;
[0065] (5) The process flow of lost foam casting is the same as that of the optimal example.
[0066] Embodiment 3, namely comparative example 4:
[0067] Reinforced ductile iron containing 0.02wt% TiC-TiB2 dual-phase hard nanoparticles was prepared using lost foam casting:
[0068] (1) The preparation and purification of TiC-TiB2 dual-phase hard nanoparticles are the same as those in the best example;
[0069] (2) weighing 0.02 wt% of the nanoparticles in the molten iron;
[0070] (3) The mixing method of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer is the same as that of the optimal example;
[0071] (4) The preparation process of the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is the same as that of the optimal example;
[0072] (5) The process flow of lost foam casting is the same as that of the optimal example.
[0073] Embodiment 4, namely comparative example 5:
[0074] Reinforced ductile iron containing 0.05wt% TiC-TiB2 dual-phase hard nanoparticles was prepared using lost foam casting:
[0075] (1) The preparation and purification of TiC-TiB2 dual-phase hard nanoparticles are the same as those in the best example;
[0076] (2) weighing 0.05 wt% of the nanoparticles by weight of the molten iron;
[0077] (3) The mixing method of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer is the same as that of the optimal example;
[0078] (4) The preparation process of the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is the same as that of the optimal example;
[0079] (5) The process flow of lost foam casting is the same as that of the optimal example.
[0080] Example 5, i.e. Comparative Example 6:
[0081] Reinforced ductile iron containing 0.08wt% TiC-TiB2 dual-phase hard nanoparticles was prepared using lost foam casting:
[0082] (1) The preparation and purification of TiC-TiB2 dual-phase hard nanoparticles are the same as those in the best example;
[0083] (2) weighing 0.08 wt% of the nanoparticles by weight of the molten iron;
[0084] (3) The mixing method of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer is the same as that of the optimal example;
[0085] (4) The preparation process of the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is the same as that of the optimal example;
[0086] (5) The process flow of lost foam casting is the same as that of the optimal example.
[0087] Example 6, i.e. Comparative Example 7:
[0088] Reinforced ductile iron containing 0.1wt% TiC-TiB2 dual-phase hard nanoparticles was prepared using lost foam casting:
[0089] (1) The preparation and purification of TiC-TiB2 dual-phase hard nanoparticles are the same as those in the best example;
[0090] (2) weighing 0.1 wt% of the nanoparticles by weight of the molten iron;
[0091] (3) The mixing method of TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer is the same as that of the optimal example;
[0092] (4) The preparation process of the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture is the same as that of the optimal example;
[0093] (5) The process flow of lost foam casting is the same as that of the optimal example.
[0094] Performance Test:
[0095] The tensile properties are in accordance with the national test standard GB / T228.1-2010. The impact properties are in accordance with the national test standard GBT229-2007. The wear resistance test is carried out on a reciprocating friction and wear tester. The upper sample is GCr15 bearing steel with a hardness of 65HRC and a surface roughness of 40-80nm. The lower sample is ductile iron with a size of 20mm (length) × 20mm (width) × 6mm (height) and a surface roughness of 150-200nm. The vertical load of the test is 40N, the reciprocating frequency is 1Hz, the test time is 30min, and the test temperature is 20℃. The test results are shown in Table 1.
[0096] Table 1. Comparison of mechanical properties and wear resistance of ductile iron with different casting processes and nanoparticle contents
[0097] name YS(MPa) UTS(MPa) εf(%) <![CDATA[ak(J / cm 2 )]]> <![CDATA[WVR(×10 -4 mm 3 )]]> Best Practices 355 517 18.4 14.6 3.63 Comparative Example 1 318 459 13.6 9.2 4.18 Comparative Example 2 320 454 14.2 9.3 4.25 Comparative Example 3 326 466 14.5 10.1 4.07 Comparative Example 4 341 485 16.3 12.9 3.85 Comparative Example 5 352 520 17.5 12.4 3.59 Comparative Example 6 358 522 12.8 10.7 3.43 Comparative Example 7 363 534 10.3 8.1 3.20
[0098] In the table: YS is yield strength, UTS is tensile strength, εf is elongation, ak is impact toughness, and WVR is volume wear rate.
[0099] It can be seen from the data in Table 1 that with the increase of the content of TiC-TiB2 dual-phase hard nanoparticles, the yield strength and tensile strength of ductile iron continue to increase, the elongation and impact toughness first increase and then decrease, and the overall wear resistance also shows an upward trend. In general, when the content of dual-phase hard nanoparticles is 0.03wt%, the comprehensive performance of ductile iron is the best.
[0100] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting, characterized in that: The following steps are involved: Step 1: Use a titanium source, a carbon source, and a boron source as precursors, wherein TiCl4 is used as the titanium source, CH4 is used as the carbon source, and B2H6 is used as the boron source. TiCl4 is slowly heated to 40°C until the gas is volatilized, and the volume ratio of TiCl4, CH4, and B2H6 is adjusted to 2:1:1 through a gas flow meter, and uniformly introduced into a high-temperature reactor filled with argon gas, and the temperature is set between 1300°C and 1400°C. TiC-TiB2 dual-phase hard nanoparticles are simultaneously deposited at the bottom of the high-temperature reactor through gas reaction, and the TiC-TiB2 dual-phase hard nanoparticles are blown out of the high-temperature reactor by the flow of argon gas and collected; Step 2: The prepared TiC-TiB2 dual-phase hard nanoparticles are repeatedly rinsed with hydrochloric acid to remove surface oxides and impurities; the rinsed TiC-TiB2 dual-phase hard nanoparticles are then rinsed with distilled water for 3 times to further remove surface impurities, and then placed in a drying furnace for drying; Step 3, putting the purified TiC-TiB2 dual-phase hard nanoparticles, aluminum powder, ductile iron inoculant and spheroidizer into a ball mill together, the ball milling time is 10 to 12 hours, and the ductile iron inoculant and spheroidizer are fully ground at the same time; Step 4: Place the nanoparticle-aluminum powder-inoculant-spheroidizer mixture after ball milling activation into alcohol, vibrate it using an ultrasonic cleaner for 40 to 60 minutes, and then place it in a drying furnace for drying; Step 5: Redissolve the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer in alcohol, and after sufficient stirring, use an ultrasonic homogenizer to disperse the mixture for 30 to 40 minutes to evenly disperse the mixture in the alcohol; Step 6: slowly put the block polystyrene material into the alcohol solution containing the mixture of nanoparticles-aluminum powder-inoculant-spheroidizer, and use an ultrasonic homogenizer to disperse the nanoparticles-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture for 60 to 80 minutes; Step 7: Place the nanoparticle-aluminum powder-inoculant-spheroidizer-polystyrene-alcohol mixture in a vacuum drying oven and slowly evaporate it until all the liquid evaporates, then take out the remaining polystyrene containing nanoparticles, aluminum powder, inoculant and spheroidizer, and cut the polystyrene into corresponding models according to the casting structure design; mix the refractory coating and water to a suitable viscosity, then evenly apply it on the surface of the polystyrene model, dry the polystyrene model, and then apply it again and dry it, repeating 3 times in total; finally, the thickness of the refractory coating on the surface of the polystyrene model is about 1 to 1.2 mm; Step 8: bury the polystyrene mold coated with refractory coating in fine sand, tap the fine sand to fix the mold, and after the mold is fixed, vibrate the mold in the X, Y, and Z directions at the same time for 30 to 50 seconds; Step nine: melt the molten iron in a medium frequency induction furnace at a temperature of 1530°C to 1540°C, and then slowly introduce the molten iron into a mold containing polystyrene through a pouring gate. After the mold cools, take out the casting and remove the sand, and finally obtain reinforced ductile iron containing dual-phase hard nanoparticles.
2. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1, characterized in that: In the step 2, the volume fraction of hydrogen chloride in the hydrochloric acid solution used is 30% to 35%.
3. The method for preparing a dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step 3, the aluminum powder used has a purity of 99.5wt%; the ductile iron inoculant used is a silicon-calcium inoculant, whose components are composed of the following weight percentages: 72.10wt% silicon, 11.51wt% calcium, 1.42wt% barium, 0.74wt% aluminum, and the balance is iron. The amount of the silicon-calcium inoculant added is 0.45wt% of the mass of the molten iron; the spheroidizer used is a rare earth magnesium-silicon-iron alloy, whose components are composed of the following weight percentages: 41.30wt% silicon, 8.22wt% magnesium, 6.22wt% cerium, 1.92wt% calcium, and the balance is iron. The amount of the spheroidizer added is 1.3wt% of the mass of the molten iron.
4. The method for preparing a dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step 4, the power of the ultrasonic cleaner used is 200W, the vibration frequency is 1kHz, the rotation speed of the ball mill used is 50rpm, the drying furnace used is a quartz tube drying furnace with a power of 450W, and the drying temperature is 130°C to 150°C.
5. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step 5, the power of the ultrasonic homogenizer used is 500W, the operating frequency is 10kHz, and the ethanol content in the alcohol solution used is 99.7%.
6. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In step six, the ethanol content in the alcohol solution used is 99.7%, and the amount used is 2.0 to 2.5 L.
7. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step six, the length×width×height of the block polystyrene material used is 100 mm×100 mm×200 mm.
8. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step seven, the components of the refractory coating used are composed of the following weight percentages: 62wt% zircon sand, 20wt% sodium silicate, 8wt% bentonite, 8wt% water, 1.5wt% dispersant, and 0.5wt% defoamer, the dispersant is carboxymethyl cellulose, and the defoamer is silicone oil. The preparation steps include: after the zircon sand, sodium silicate and bentonite are fully mixed, water is added and continuous stirring is continued, after the mixture is evenly mixed, the dispersant and defoamer are added, and continuous stirring is continued until the mixture is evenly mixed.
9. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In the step 7, the power of the vacuum drying oven used is 1000W, the drying temperature is 40°C to 50°C, and the drying time is 20 to 30 minutes.
10. The method for preparing dual-phase hard nanoparticle reinforced ductile iron for lost foam casting according to claim 1 or 2, characterized in that: In step nine, the molten iron used is composed of the following weight percentages: 3.64wt% carbon, 2.78wt% silicon, 0.40wt% manganese, 0.003wt% phosphorus, 0.015wt% sulfur, 0.035wt% magnesium, 0.012wt% titanium, 0.015wt% aluminum, and the balance is iron.
Citation Information
Cited By
High-strength and high-toughness nodular cast iron material and preparation method thereof
CN121183213A
High-strength high-toughness nodular cast iron material and method for producing the same
CN121183213B